Water Quality Assessment of Lakes (Ain Al-Ghazala and Umm-Hufayn) for Fish Culture in the Eastern Coast of Libya - Fitori, Amani F.; Al-Mismari, Anwar A. R.; Mahdy, Aldoushy A.; Said, Rashad E.M.; Masoud, Ashraf N. (Al-Mukhtar Journal of Sciences, 2022)
Assessments of some physical and chemical properties were conducted  for two Libyan water bodies (Ain Al- Ghazala and Umm-Hufayn). Of each ecosystem, ten water samples were taken from ten points for analysis. The results showed that the electric conductivity in Ain Al-Ghazala Bay waters is higher than that in the waters of Umm-Hufayn Lake. In the two areas, the hydrogen ion concentration pH recorded the highest value with a value of 8.3, with mean values of chloride (Cl) exceeding the internationally recorded limits. Furthermore, nitrites (NO2), nitrate (NO3), sulphate (SO4), phosphate (PO4), silicates (SiO2), carbonate (CO3), calcium (Ca), magnesium (Mg), sodium (Na), and potassium (K) were all greater in Ain Al-Ghazala Bay waters than in Umm-Hufayn Lake waters. In conclusion, more attention should be directed to the preservation of such natural resources.